Hellenistische Häuser in Lousoi. Keramik und Kleinfunde aus den Grabungen 1983-1994 - Mitsopoulos-Leon, Veronika (Holzhausen, 2017)
Subject of the volume are the finds uncovered during the excavations of the ÖAI in the residential area "Phournoi" of the ancient town of Lousoi in Northwest Arkadia. A short introduction to the architecture of the houses is followed by the presentation of the pottery and small finds in their chronological and functional context. This study results in important information concerning daily life, domestic culture and the economic background of the region mainly in the Hellenistic period.